Dynamic Concentric Activity Can Increase the GLUT-1 Expression on Muscle Membrane on Diabetic Mice - Yusuf, Havid; Safitri, Dini (Folia Medica Indonesiana, 2018)
Diabetes mellitus is a type of a degenerative disorder that affects the body's ability to make or use insulin. The resistance of insulin may affect the decline of GLUT-1 expression of diabetic muscle, causing impaired glucose uptake. Dynamic concentric activity is one of the activity models based on muscle-contraction-type activity. This study used experimental method. The instrument in this study was a treadmill (brand: modified columbus treadmill) with 10-degree slope (uphill), with the velocity of 21 cm/sec (the speed options showed on the treadmill), and the duration of the exercise was 16 minutes and 30 seconds (measured using stopwatch). In this study, there were 3 groups of samples, Normal (K0), DM (K1), and DM + Dynamics Concentric (K2). Based on statistical results of correlation value p=0.00 (p<0.05), there was significant correlation between blood sugar level and GLUT-1. Dynamic concentric activity for diabetics had an effect in increasing the amount of GLUT-1, resulting in decreased blood glucose levels.